2019
DOI: 10.1016/j.isci.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Current Generator Based on Dynamic PN Junctions with the Designed Voltage Output

Abstract: SummaryThe static PN junction is the foundation of integrated circuits. Herein, we pioneer a high current density generation by mechanically moving N-type semiconductor over P-type semiconductor, named as the dynamic PN junction. The establishment and destruction of the depletion layer causes the redistribution and rebounding of diffusing carriers by the built-in field, similar to a capacitive charge/discharge process of PN junction capacitance during the movement. Through inserting dielectric layer at the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 58 publications
1
93
0
Order By: Relevance
“…[ 5 ] Recently, it was found that the CE will be very different when the semiconductor is involved. [ 6 ] The current can be generated by the contact or sliding of a P‐type semiconductor against an N‐type semiconductor [ 7–9 ] (or semiconductor against metal [ 10–12 ] ), and a novel electric generator was proposed. [ 7 ] This new type of electric generator is gaining attention for that a direct current can be generated without a rectifier module.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Recently, it was found that the CE will be very different when the semiconductor is involved. [ 6 ] The current can be generated by the contact or sliding of a P‐type semiconductor against an N‐type semiconductor [ 7–9 ] (or semiconductor against metal [ 10–12 ] ), and a novel electric generator was proposed. [ 7 ] This new type of electric generator is gaining attention for that a direct current can be generated without a rectifier module.…”
Section: Figurementioning
confidence: 99%
“…[ 7 ] This new type of electric generator is gaining attention for that a direct current can be generated without a rectifier module. [ 8–11 ] However, the mechanism of the current generation in the CE involving semiconductors is still under debate.…”
Section: Figurementioning
confidence: 99%
“…In 2012, Wang's group invented the triboelectric nanogenerator (TENG) based on contact electrification and electrostatic induction ( Li et al, 2020a , 2020b ; Wang, 2013 ). With the gifted advantages such as simple structure, abundant material options, and low fabrication cost ( Wang, 2014 ; Wang et al., 2015 ; Zhang et al., 2014 ; Zhao et al., 2019 ), the TENGs have made remarkable achievements in the application field of micropower/nanopower sources ( Ahmed et al., 2020 ; Chandrasekhar et al., 2017 ; Deng et al., 2020 ; Jin et al., 2020 ; Liu et al., 2020a ; Lu et al., 2019 ; Quan et al., 2015 ; Šutka et al., 2020 ; Yan et al., 2020 ; Yang et al., 2013 , 2014 ; Zou et al., 2020 ), self-powered sensors ( Bu et al, 2018a , 2018b ; Fu et al., 2017 ; Guo et al., 2018 ; Meng et al., 2020 ; Pang et al., 2015 ; Su et al., 2020a , 2020b ; Wang et al., 2018a ; Zhou et al., 2020b , 2020c ), high-voltage power sources ( Bu et al., 2019 ; Fan et al., 2015 ; Nie et al., 2018 ; Yang et al., 2019a ), and large-scale blue energy ( Chen et al., 2020b ; Liang et al., 2019 ; Rodrigues et al., 2020 ; Xu et al, 2017 , 2018 ; Yang et al., 2019b ; Zhang et al., 2016a ), which is to harvest the low frequency, irregular, and multidirectional water wave energy. Recently, some remarkable works have been developed to improve the performance of TENGs ( Liu et al., 2020b , 2020c ; Wang et al., 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the full potential of TENG from new structures to realize DC output is highly desired for accelerating the miniaturization of IoTs and self-powered systems and may promote the understanding of TENG and CE from a new horizon. Besides the above-mentioned DC-TENG, there are still other DC generators have been reported based on Schottky knot, silicon p-n junction, contact barrier between metal and semiconductor, and tunneling effect in metal-insulator-semiconductor structure ( Lin et al., 2019 ; Liu et al., 2018a , 2018b , 2019b ; Lu et al., 2019 ; Shao et al., 2019a ; Xu et al., 2019a ; Zhang et al., 2018a , 2018b , 2020c ), in which the most basic mechanism for charge transfer is still CE. These generators can be considered as the general DC-TENG.…”
Section: Summary and Perspectivesmentioning
confidence: 99%